Geometrical modeling of the shape of a multilink rod structure in weightlessness under the influence of pulses on the end points of its links - Kutsenko, Leonid; Semkiv, Oleg; Zapolskiy, Leonid; Shoman, Olga; Ismailova, Nelli; Vasyliev, Serhii; Adashevska, Irina; Danylenko, Volodymyr; Pobidash, Andrey (Eastern-European Journal of Enterprise Technologies, 2018)
We have examined a geometrical model of the new technique for unfolding a multilink rod structure under conditions of weightlessness. Displacement of elements of the links occurs due to the action of pulses from pyrotechnic jet engines to the end points of links in a structure. A description of the dynamics of the obtained inertial unfolding of a rod structure is performed using the Lagrange equation of second kind, built using the kinetic energy of an oscillatory system only. The relevance of the chosen subject is indicated by the need to choose and explore a possible engine of the process of unfolding a rod structure of the pendulum type. It is proposed to use pulse pyrotechnic jet engines installed at the end points of links in a rod structure. They are lighter and cheaper as compared, for example, with electric motors or spring devices. This is economically feasible when the process of unfolding a structure in orbit is scheduled to run only once. We have analyzed manifestations of possible errors in the magnitudes of pulses on the geometrical shape of the arrangement of links in a rod structure, acquired as a result of its unfolding. It is shown at the graphical level that the error may vary within one percent of the estimated value of the magnitude of a pulse. To determine the moment of fixing the elements of a multilink structure in the preset unfolded state, it is proposed to use a «stop-code». It is a series of numbers, which, by using functions of the generalized coordinates of the Lagrange equation of second kind, define the current values of angles between the elements of a rod structure. Results are intended for geometrical modeling of the unfolding of large-size structures under conditions of weightlessness, for example, power frames for solar mirrors, or cosmic antennae, as well as other large-scale orbital facilities.